KEEFEKTIFAN METODE FOUR SQUARE WRITING BERBANTUAN INFOGRAFIS DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI - Maghfirah, Almalika Nadiya; Pratiwi, Wienike Dinar; Suntoko, Suntoko (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the effectiveness of Four Square Writing method assisted by infographics in learning to write biography text. This type of research is a quasi-experiment. The sample was 64 students of class X SMAN 1 Klari. Data collection techniques were conducted through observation and biography text writing test. The research data were analysed using descriptive and infersential statistics. The results showed that there was a significant increase in the ability to write biography text on the posttest of the experimental class. Meanwhile, the ability to write biography text on the control class posttest has not shown a significant improvement. Based on the hypothesis test, the result of Sig. (2-tailed) of 0.001 <0.05. This shows that the application of Four Square Writing method assisted by infographic image media is effective in learning to write biographical texts for class X students of SMAN 1 Klari.